Systemic Racism and Othering within Government Agencies: A Psychoanalytic Interpretation of Environmental Injustice in the Flint, Michigan Water Crisis. Issue 1 (1st January 2021) - Rudden, Marie G.
ABSTRACT: The severe water emergency in Flint, Michigan between 2014 and 2016 was inarguably caused by systemic organizational dysfunction. The Michigan Governor Snyders' Flint Water Advisory Task Force, in their analysis of the severe water emergency in Flint, Michigan, emphasized the degree of systemic organizational dysfunction, providing evidence that the agencies involved demonstrated a disregard for the poor and black citizens of Flint and participated in environmental injustice. The author traces, through journalists' reports, e-mails between and among officials, first-hand testimony and the timeline provided by the Task Force, that the performance of the involved agencies (the state Department of Environmental Quality and the Michigan Department of Health Services) was tainted by systemic racism, Othering and by the dehumanization of Flint citizens the majority of whom were African American, and poor. The scandal was finally made public when a pediatrician showed unequivocal data on the alarmingly high lead levels in children who ingested the water. An organizational analysis based on psychoanalytic principles (Freud, Bion, Hopper) further supplements her observations that systemic racism aided and abetted severe systemic dysfunction.